85.3k views
0 votes
Given the definitions of f(x) and g(x) below, find the value of (gof)(1).f(x) = 2x2 – 22 – 4g(x) = 5x = 14

Given the definitions of f(x) and g(x) below, find the value of (gof)(1).f(x) = 2x-example-1
User Treemonkey
by
5.8k points

1 Answer

6 votes

Given:

f(x) = 2x^2-2x-4.

g(x) = -5x+14.

The objective is to find the value of (gof) (1).

The (gof) (x) can be calculated as,


\begin{gathered} (g\circ f)(x)=g(f(x)) \\ =-5(2x^2-2x-4)+14 \\ =-10x^2+10x+20+14 \\ =-10x^2+10x+34 \end{gathered}

Now, substitute x= 1 in the above function.


\begin{gathered} (g\circ f)(x)=-10(1)^2+10(1)+34 \\ =-10+10+34 \\ =34 \end{gathered}

Hence, the value of (gof) (1) is 34.

User Mutp
by
5.7k points